2010
DOI: 10.1001/jama.2010.926
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced HIV Seropositivity/Reactivity in Noninfected HIV Vaccine Recipients

Abstract: Context Induction of protective anti-HIV immune responses is the goal of an HIV vaccine. However, this may cause a reactive result by routine HIV testing in the absence of HIV infection. Objective This study evaluated the frequency of vaccine-induced seropositivity/reactivity (VISP) in HIV vaccine trial participants. Design, Setting, and Participants A routine diagnostic HIV algorithm was used for participants who completed 25 phase 1 and two phase 2 vaccine trials from 2000–2010 conducted in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 29 publications
(33 reference statements)
0
36
0
Order By: Relevance
“…18 In persons with vaccineinduced seropositivity, serial testing or multi-test algorithms are required to maintain the specificity of true infection endpoints for the trial data and for the participants. 19 Thus, the first step toward obtaining accurate malaria diagnostics is to ensure that the appropriate assay is selected. The appropriate assay will depend on trial-specific research/ clinical question(s) and the epidemiologic environment at the study site(s).…”
Section: Introductionmentioning
confidence: 99%
“…18 In persons with vaccineinduced seropositivity, serial testing or multi-test algorithms are required to maintain the specificity of true infection endpoints for the trial data and for the participants. 19 Thus, the first step toward obtaining accurate malaria diagnostics is to ensure that the appropriate assay is selected. The appropriate assay will depend on trial-specific research/ clinical question(s) and the epidemiologic environment at the study site(s).…”
Section: Introductionmentioning
confidence: 99%
“…1 Vaccine-induced seropositivity (VISP) is a common outcome of HIV vaccine trials, 2 mostly associated with vaccines containing envelope inserts. [2][3][4][5][6] Current HIV screening policy relies on highly sensitive enzyme immunoassays detecting antibodies against different proteins, most often p24, HIV-1 gp41 and HIV-2 gp36. Although 4th generation tests reduce the size of the diagnostic window by combining HIV antibody and p24 antigen detection, 7-10 many clinical laboratories still use 3rd generation assays.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 41.7% of HIV vaccine recipients in 27 HIV Vaccine Trials Network (HVTN)-sponsored HIV vaccine trials of 25 different vaccine products, conducted between 2000 and 2010, were found to exhibit VISP at the trial exit date when VISP was surveyed across multiple serological kits (9). VISP frequencies ranging from 6% to as high as 80% to 100% have been associated with vaccination protocols employing adenovirus (9,10) and modified vaccinia virus Ankara (MVA) (32), depending on which serological kits were used. In contrast, low levels of VISP were observed in RV144 vaccine recipients tested with the Vironostika HIV-1 kit, although the same kit yielded divergent results in other trials (8,9) (HVTN, unpublished data).…”
mentioning
confidence: 99%
“…VISP frequencies ranging from 6% to as high as 80% to 100% have been associated with vaccination protocols employing adenovirus (9,10) and modified vaccinia virus Ankara (MVA) (32), depending on which serological kits were used. In contrast, low levels of VISP were observed in RV144 vaccine recipients tested with the Vironostika HIV-1 kit, although the same kit yielded divergent results in other trials (8,9) (HVTN, unpublished data). VISP peaked 6 months following the final vaccination, at which time seroreactivity was detected by the Vironostika kit in 28 (0.4%) of 7,015 tested vaccine recipients, compared to 4 (0.06%) of 7,099 tested placebo recipients (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation